Internalisasi Internalization of Social Awareness Values in Islamic Religious Education Learning - Muhammad Ma'ruf; Muhammad Thoif; Izzatul Laili (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze the strategy of internalizing social awareness values in Islamic Religious Education (PAI) learning at Mandala Trikora Private High School in Jayapura City in a multicultural school context. The method used is a qualitative approach with a case study type. Data were collected through observation, interviews with PAI teachers and students, and documentation. Data analysis used the Miles and Huberman model through reduction, presentation, and conclusion, with validity testing through triangulation of sources and methods. The results show that internalization of social awareness values occurs through three stages, namely value transformation, value transactions, and value internalization. This process is supported by the integration of contextual learning materials, the use of collaborative methods, interactive media, social behavior habits, and teacher role models. As a result, students not only understand the values of social awareness cognitively, but are also able to internalize and implement them in real behaviors such as empathy, tolerance, cooperation, and mutual assistance. However, there are obstacles in the form of environmental influences, social media, and lack of family support. Overall, PAI learning is effective as a means of internalizing values in shaping students' social character holistically.